Estudio geológico estructural a escala 1:25000 de la parroquia Cruzpamba, cantón Celica, provincia de Loja - Rodríguez Chamba, Josselyn Nicole (2024)
The Cruzpamba parish is located in the South of Ecuador, province of Loja, canton Celica, and covers an area of 26.79km². Delimited to the north by the San Juan de Pózul and Celica parishes; to the south by the Teniente Maximiliano Rodríguez and Celica parishes; to the east by the Celica parish and to the west by the San Juan de Pózul and Teniente Maximiliano Rodríguez parishes. The investigative work was developed in three phases: prefield phase where bibliographic information on the area was collected; field phase in which in situ information such as topography, geology and structural geology was collected and corroborated; office phase that consisted of the processing and interpretation of information and the creation of maps. The geological-structural survey of the Cruzpamba parish was carried out at a scale of 1:25,000. For the geological characterization, photointerpretative analysis was used, the contact mapping method was used and it was complemented with outcrop mapping in a total of 64 outcrops for better corroboration of the present geology, this is how it was possible to identify the presence of 4 lithological formations, each with characteristics specific to each lithology: the Celica Formation (Lower Cretaceous) constituted as the basement of the study area to share the largest amount of surface with 25.51 km² made up of volcanic tuffs, tuffs with hematite, andesites and basaltic andesites; The Ciano Formation (Upper Cretaceous) has an area of 0.45km² made up of sedimentary volcanic rocks of lithified sandstones and siltstones; Alluvial deposit (Quaternary) with an area of 0.39 km² consisting of a silt-sandy matrix with fragments of andesite rock; Colluvial deposit (Quaternary) that occupies an area of 0.46 km² composed of angular andesitic materials. Regarding the structures in the study area, none were identified through photointerpretive analysis; however, in the field the presence of deformation structures is evident, such as joints present in siltstone and basaltic andesite rocks, as well as a quartz vein evident in andesite rock. Keywords: Contact mapping, geological survey, structural geology, photointerpretive analysis